2020
DOI: 10.5653/cerm.2020.04126
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in the uterine vessel microenvironment: Balancing vasoactive factors

Abstract: Autophagy, which has the literal meaning of self-eating, is a cellular catabolic process executed by arrays of conserved proteins in eukaryotes. Autophagy is dynamically ongoing at a basal level, presumably in all cells, and often carries out distinct functions depending on the cell type. Therefore, although a set of common genes and proteins is involved in this process, the outcome of autophagic activation or deficit requires scrutiny regarding how it affects cells in a specific pathophysiological context. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Autophagic defects are generally visualized by examining SQSTM1 accumulation [ 1 ] because it is highly upregulated when autophagic flux is blocked [ 12 ]. In Atg7 f/f (wild-type) virgin uteri, autophagy is generally active, and there was no visible accumulation of SQSTM1 ( Figure 1 , virgin Atg7 f/f ), which was consistent with the results of our previous study [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagic defects are generally visualized by examining SQSTM1 accumulation [ 1 ] because it is highly upregulated when autophagic flux is blocked [ 12 ]. In Atg7 f/f (wild-type) virgin uteri, autophagy is generally active, and there was no visible accumulation of SQSTM1 ( Figure 1 , virgin Atg7 f/f ), which was consistent with the results of our previous study [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…While it takes place at a basal level in all tissues, the consequences of autophagy deficiency vary significantly depending on the tissue type. In the mouse uterus, autophagy levels differ between epithelial and mesenchymal tissues [ 1 ]. We have previously demonstrated that the uterine mesenchyme, including the stroma, myometrium, and endothelial smooth muscle cells, is a site of active autophagic turnover in mice [ 2 ].…”
Section: Introductionmentioning
confidence: 99%